2019
DOI: 10.1038/s41598-019-51331-5
|View full text |Cite
|
Sign up to set email alerts
|

Storage and erasure of behavioural experiences at the single neuron level

Abstract: Although predictions from the past about the future have been of major interest to current neuroscience, how past and present behavioral experience interacts at the level of a single neuron remains largely unknown. Using the pond snail Lymnaea stagnalis we found that recent experience of terrestrial locomotion (exercise) results in a long-term increase in the firing rate of serotonergic pedal (PeA) neurons. Isolation from the CNS preserved the “memory” about previous motor activity in the neurons even after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…All values are given as median with the lower and upper quartiles * indicates p < 0.05. from the breeding stock (Kruskal-Wallis test: H (2, N = 91) = 7.5, p = 0.0234; Figure 2C, post hoc tests ER/Ch p = 0.020; ER/Cn p = 0.2; Ch/Cn p = 0.9). Recently, we reported that locomotor arousal developed more quickly in the ER snails than in the Cn group (Dyakonova et al, 2019). Similar trend can be seen in Figure 3D.…”
Section: The Delayed Effects Of Intense Locomotion On Decision-makingsupporting
confidence: 85%
See 3 more Smart Citations
“…All values are given as median with the lower and upper quartiles * indicates p < 0.05. from the breeding stock (Kruskal-Wallis test: H (2, N = 91) = 7.5, p = 0.0234; Figure 2C, post hoc tests ER/Ch p = 0.020; ER/Cn p = 0.2; Ch/Cn p = 0.9). Recently, we reported that locomotor arousal developed more quickly in the ER snails than in the Cn group (Dyakonova et al, 2019). Similar trend can be seen in Figure 3D.…”
Section: The Delayed Effects Of Intense Locomotion On Decision-makingsupporting
confidence: 85%
“…No measurable FIGURE 1 | Schematic representation of the experimental procedure. (A) Procedure for the investigation of the effects of enhanced motor activity (exercise, E, EE) and rest after exercise (ER), redrawn after (Korshunova et al, 2016;Dyakonova et al, 2019). In double-blind experiments, snails were divided into control and experimental groups and resided in similar light conditions before being placed in the test arena.…”
Section: Test For Behavior In the Novel Environment (Experiments 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Reconsolidation of a contextual memory has been shown in invertebrate animals [49,[56][57][58][59][60][61]. The investigation of the memory formation process and memory reconsolidation in mollusks is also attractive due to the possibility of investigate the correlations between memory mechanisms and changes occurs at the cellular and receptor level [40,[62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%